An Overview of Current Recommendations and Options for the Management of Cancer Pain: A Comprehensive Review - Gress, Kyle L. (Oncol Ther, 2020)
It is estimated that one-third of oncologic patients in the USA do not receive analgesia proportional to or adequate for the intensity of their pain. A mechanism-based approach to oncologic pain therapy is critical to ensure that analgesia regimens are individualized and effective. Since the mechanisms that lead to cancer pain are complex, healthcare providers must be willing to elicit and recognize the symptoms of each individual patient since these factors influence both the experience of pain and response to treatment. This process is centered on the use of detailed history in order to understand symptom expression in the context of primary tumor diagnosis and progression, history of cancer pain, psychological distress, sleep disturbances, cognitive function, and addictive behavior. Incorporating all of these factors into the assessment of a patient’s pain condition can facilitate management decisions and help predict patient response to treatment.